Children of prisoners: a growing public health problem - Simon Quilty; Michael H. Levy; Kirsten Howard; Alex Barratt; Tony Butler (Elsevier, 2004)
Abstract Objectives:To estimate the number and proportion of children in New South Wales affected by parental incarceration, and to describe the health impact of punitive incarceration on the children of prisoners. Methods:In 2001, NSW Corrections Health Service conducted a cross‐sectional survey of prison inmates randomly selected from each of the 29 prisons in NSW, representing 11% of male and 30% of female inmates in the State. The survey included questions regarding parental status and number of children. A population model was developed, which incorporated increases in the prison population and recidivism, to estimate the number of children under 16 years of age in NSW ever having experienced parental incarceration. Results:In 2001, there were approximately 14,500 children under the age of 16 years in NSW who experienced parental incarceration during the year. It is estimated that in 2001 there were 60,000 children under 16 years in NSW who had ever experienced parental incarceration in their lifetime, representing 4.3% of all children and 20.1% of Indigenous children. Conclusions:The number of children who have experienced parental incarceration is significant in NSW and across Australia. Indigenous children are much more likely to experience parental incarceration than non‐Indigenous children. Implications:Children of prisoners are at high risk of negative health outcomes and are themselves at an increased risk of offending later in life. The needs of these children must be recognised and policies introduced to reduce the adversities they face. The social, politico‐legal and economic conditions that are contributing to the continuing rise in incarceration rates must be recognised, and measures must be taken to reduce this trend.